The Linguistic Meaning Between Traditional Rhetorical Frameworks and Artificial Intelligence Models: A Post humanist Critique of Computational Semantics - Al-Dadi, Muqbil bin Ali (Journal of Posthumanism, 2025)
This research explores the radical transformations in the concept of linguistic meaning following the emergence of Large Language Models (LLMs) and their impact on our understanding of semantics and signification, offering a posthumanist critique of computational semantics. The study compares the mechanisms of meaning-making in these models with the traditional conceptions of meaning articulated by classical Arab scholars, particularly Abd al-Qahir al-Jurjani's "Theory of Nazm" (Coherence/Arrangement) and Ibn Jinni's insights into the relationship between word and meaning. The research poses fundamental questions about the nature of meaning in intelligent models: Is it genuine meaning or a mere simulation? And how do these models redefine our understanding of humanity and consciousness? It investigates the potential of traditional Arab linguistic frameworks to offer a critical alternative to the contemporary understanding of artificial intelligence, emphasizing the importance of deep, contextual understanding in the face of statistical comprehension. The study includes an applied analysis of the Riyadh Dictionary as a model for the computational processing of meaning in the Arabic language.